Invasion dynamics of Acer negundo L. in ribbon forests of the Altai Krai: ecological impacts and predictive habitat modeling - Natalia V. Ovcharova; Marina M. Silantyeva; Alexey V. Vaganov; Anastasia A. Masanina (Acta Biologica Sibirica)
This study examines the invasion dynamics of ash-leaved maple (box elder, Acer negundo L.) in the ribbon forests of Altai Krai, Russia, where it has become one of the dominant invasive species over the past thirty years. Originally introduced as an ornamental plant in the early 20th century, A. negundo has rapidly proliferated in lowland, steppe, and forest-steppe regions, significantly impacting local ecosystems. Our research analyzes the ecological and phytocoenotic conditions that facilitate A. negundo's invasion, focusing on its distribution across various ribbon pine forests in the region. Through geobotanical surveys and forest management record analysis, we reveal the species' prevalence in diverse forest types and its effects on biodiversity, tree growth, and community dynamics. Key findings indicate that A. negundo flourishes in disturbed habitats, where it aggressively competes with native flora, suppressing their growth and altering successional pathways. This leads to low-diversity communities increasingly dominated by the invasive species and highlights the exacerbating role of logging and land-use changes. Using predictive modeling techniques, we assessed habitat suitability for A. negundo across Eurasia, identifying temperature as the primary limiting factor for its distribution. The model achieved a high AUC value of 0.97, indicating strong reliability. These findings suggest a significant potential for A. negundo's range expansion throughout Altai Krai, especially in areas with reduced competition from native species. This research underscores the urgent need for effective management strategies to mitigate the effects of A. negundo in Altai Krai and similar regions.